Students’ Attitude toward Mathematics and its Relationship with Mathematics Achievement - Hwang, Sunghwan; Son, Taekwon (Journal of Education and e-Learning Research, 2021)
The relationship between students’ attitudes toward mathematics and mathematics achievement has garnered tremendous attention from researchers. However, there is a degree of inconsistency in the findings regarding this relationship. Therefore, this study aimed to identify the profiles of students’ attitudes toward mathematics and examine their relationship with mathematics achievement. Using latent profile analysis, we examined data from the Trends in International Mathematics and Science Study conducted in Singapore in 2019. We identified four profiles of attitudes toward mathematics, namely very negative (5.44%), negative (41.38%), neutral (38.77%), and positive (14.41%). We also confirmed the literature describing students’ attitude toward mathematics as a multidimensionally integrated construct, comprising ‘like mathematics,’ ‘value mathematics,’ and ‘confidence in mathematics.’ Moreover, we discovered a positive relationship between students’ attitudes toward mathematics and mathematics achievement. These results showed that the following students are more likely to have high mathematics achievement: (a) those who like to study mathematics and pursue mathematics-related activities, (b) those who believe that learning mathematics will result in a positive outcome (e.g., success in school and job opportunities), and (c) those who trust in their mathematical abilities. Therefore, educators need to examine students’ attitudes toward mathematics and provide appropriate support to stimulate the development of a positive attitude toward mathematics.